Підготовка майбутніх учителів музичного мистецтва до керівництва ансамблем в ЗЗСО - Мельниченко Юлія; Melnychenko Yuliia; Мельниченко Максим; Melnychenko Maksym; Літвін Катерина; Litvin Kateryna (Видавництво «Код», 2025)
Резюме. У статті автори розглядають особливості та зміст підготовки здобувачів вищої освіти до керівництва ансамблевим музикуванням учнів закладів загальної середньої освіти. Підкреслено, що цей процес є багатоаспектним і включає мотиваційно-ціннісний, методично-когнітивний, діяльнісно-практичний та інформаційно-технологічний компоненти, які в єдності забезпечують формування професійної компетентності майбутнього вчителя музичного мистецтва.

Abstract. In the article, the authors examine the features and content of preparing higher education students for leading ensemble music-making among secondary school students. It is emphasized that this process is multifaceted and includes motivational and value-based, methodological and cognitive, activity-practical, and informational-technological components, which together ensure the formation of professional competence in future music teachers. The role of the motivational and value-based component in developing students’ creative activity and professional orientation is defined; the methodological and cognitive component – in forming the knowledge necessary for organizing ensemble activities; and the activity-practical component – in acquiring performance and communicative skills. Special attention is given to the informational-technological component, which involves the use of modern digital tools, audiovisual resources, and educational platforms in the process of students’ training. It is noted that the integration of these components forms a comprehensive readiness of higher education students for effective leadership in ensemble music-making, meeting the requirements of modern art education and the trends of the digital age. The considered motivational-value, methodological-cognitive, activity-practical and information-technological components in their unity ensure the systematicity and integrity of the training of the future teacher, contributing to the formation of his pedagogical skills, creativity and ability for artistic and communicative interaction. Thus, the combination of these components forms a comprehensive readiness of higher education students for effective leadership of ensemble music making, which meets the requirements of modern art education and the trends of the digital age.
Preparation of future music teachers for leading an ensemble in general secondary education institutions
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: ансамбль; ансамблеве музикування; професійна підготовка; музичне мистецтво; методична компетентність; інформаційно-технологічний компонент